2012
DOI: 10.2147/ccide.s7837
|View full text |Cite
|
Sign up to set email alerts
|

Advances in dental veneers: materials, applications, and techniques

Abstract: Laminate veneers are a conservative treatment of unaesthetic anterior teeth. The continued development of dental ceramics offers clinicians many options for creating highly aesthetic and functional porcelain veneers. This evolution of materials, ceramics, and adhesive systems permits improvement of the aesthetic of the smile and the self-esteem of the patient. Clinicians should understand the latest ceramic materials in order to be able to recommend them and their applications and techniques, and to ensure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…The master model in this study was fabricated from epoxy resin as it does not interfere with the removal of the impressions and its ability to hold the reference marks in its place due to the high dimensional accuracy of this type of resin [1] . The control group, impressions were poured without surface treatment while in sterilization group, the impressions were autoclaved for 15 minutes at 134 o c in accordance with Holtan J.et al, [9] as they reported that autoclaving of the impression for 15 minutes at 134°C is enough to kill microbial spores. In the disinfection group, the impressions were immersed in (2%glutraldehyde) solution for 30 minutes as this technique was proved by Herrera and Merchant, [20] to be the most reliable disinfection method because the immersion of the impression ensures that the disinfectant solution comes into contact with all the impression material surfaces and the tray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The master model in this study was fabricated from epoxy resin as it does not interfere with the removal of the impressions and its ability to hold the reference marks in its place due to the high dimensional accuracy of this type of resin [1] . The control group, impressions were poured without surface treatment while in sterilization group, the impressions were autoclaved for 15 minutes at 134 o c in accordance with Holtan J.et al, [9] as they reported that autoclaving of the impression for 15 minutes at 134°C is enough to kill microbial spores. In the disinfection group, the impressions were immersed in (2%glutraldehyde) solution for 30 minutes as this technique was proved by Herrera and Merchant, [20] to be the most reliable disinfection method because the immersion of the impression ensures that the disinfectant solution comes into contact with all the impression material surfaces and the tray.…”
Section: Discussionmentioning
confidence: 99%
“…There are four types of elastomeric impression materials available for crown and fixed partial denture fabrication: addition silicone, condensation silicone, polysulfide, and polyether. Accuracy and dimensional stability are two principal characteristics of the impression material [9] . The accuracy of an impression material is dependent on the dimensional stability, which is the ability of an impression material to maintain the accuracy of the impression over the time.…”
Section: Introductionmentioning
confidence: 99%
“…Dental ceramics can both improve teeth's aesthetic appearance and reestablish their strength and function [10, 27]. When comparing ceramic veneers with composite resins, we can see that the ceramics offer substantial improvements in optical behavior, color stability, shape, surface smoothness, and mechanical and physical properties; ceramic veneers emulate the shape of the dental tissue to be replaced or repaired [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Положительные физические, биологические и эстетические свойства дисиликата лития были не-однократно доказаны при применении в лечении изменения цвета зубов [1,12]. Современная мало-инвазивная методика использования данного мате-риала помогла выйти на новый уровень лечения па-циентов с изменениями цвета зубов.…”
Section: результаты и обсуждениеunclassified